Semiotic Construction of an Intensive Multimedia Environment on a Cognitive Basis - Ð. Mordvinov, V.; B. Plotnikov, S. (International Journal of Engineering and Technology, 2018)
Materials of this article are scientific-methodological development of a state-funded academic research work titled: â€œResearching Cognitive Semiotics in a Virtual Reality Multimedia Environmentâ€ that reflects intermediary results of the second year of the mentioned research. According to the task, a concept of model solution was built, with an introduction of a series of updating notions. This article presents it as paradigmatics on creating the projectâ€™s basic ontology and mathematical models that display the model created by executors of the structural-semiotological methodology of system arrangement of virtual environments and multimedia production.The obtained results and recommendations are used by the Moscow Technological Universityâ€™s Information Technologies Institute (MTUITI), department of Instrumental and Applied Software (IAS) for the course of â€œMethodological IT Fundamentalsâ€ for masterâ€™s students specializing in â€œProgram Engineeringâ€ (â€œIS Architectureâ€ profile), for mastersâ€™ and bachelorsâ€™ qualification paper topics, and for post-graduate work. This paper can be helpful for professors, supporting staff, tutors and instructors, as well as, by all of the students of IAS and MTUITIÂ Â